Music and Theater in Minnesota History - Sherman, John K. (Book collections on Project MUSE., 1958)
Music and Theater in Minnesota History was first published in 1958. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.